Structural imbalances of the Russian labor market in the context of demographic decline ("Journal "U". Economy. Management. Finance.", 2025)
Abstract. The paper analyzes structural imbalances of the Russian labor market under demographic decline, including the shrinking working age population, workforce aging, regional disparities, and challenges in migration policy. Solution pathways are proposed.
Keywords: labor market; demographic decline; structural imbalances; migration policy; professional retraining